Дикие животные сказки - Петрушевская Людмила Стефановна (Эксмо, 2019)
Экземпляры: аб (20211208) / Инвентарный номер: 57682 / Цена: 596.47 / Сис.шифр: Р2 / Авт.знак: П 31 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44